Effects of gradient transitional layer on thermal cycling life and failure of LaZrCeO/YSZ thermal barrier coatings. (February 2020) - Shen, Zaoyu; He, Limin; Mu, Rende; Xu, Zhenhua; Huang, Guanghong
Highlights: The LaZrCeO/YSZ with GTL showed relativity good thermal cycling life and thermal stability. After thermal cycles, the Cr element diffuses out and concentrates in LaZrCeO layer. The crack evolution and diffusion behavior appear to be relevant with the failure mechanism. Abstract: The present work focuses on investigation of the effects of gradient transitional layer (GTL) on thermal cycling life and failure behavior of LaZrCeO/YSZ thermal barrier coatings. Characterization of microstructure evolution is implemented using correlative methods, which links together the observations and analysis from X-ray diffraction, scanning electron microscopy and transmission electron microscopy. The LaZrCeO/YSZ with GTL showed relatively good thermal cycling life and thermal stability. After thermal cycles, Cr element diffuses out and concentrates in LaZrCeO layer. The crack evolution, diffusion behavior and thermal stability are the key factors for the good thermal cycling life and failure mechanism of LaZrCeO/YSZ.